2020
DOI: 10.1371/journal.pone.0238726
|View full text |Cite
|
Sign up to set email alerts
|

Using speech recognition technology to investigate the association between timing-related speech features and depression severity

Abstract: Background There are no reliable and validated objective biomarkers for the assessment of depression severity. We aimed to investigate the association between depression severity and timingrelated speech features using speech recognition technology. Method Patients with major depressive disorder (MDD), those with bipolar disorder (BP), and healthy controls (HC) were asked to engage in a non-structured interview with research psychologists. Using automated speech recognition technology, we measured three timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…A study using different languages such as English [31] and Japanese [32] have shown that timingbased feature is a promising biomarker for depression speech. Initial studies on pauses and silence found that pause time was longer for depressed patients than in healthy speech.…”
Section: Comparison Of Classifiers Performance On Depressed Speech Classificationsmentioning
confidence: 99%
“…A study using different languages such as English [31] and Japanese [32] have shown that timingbased feature is a promising biomarker for depression speech. Initial studies on pauses and silence found that pause time was longer for depressed patients than in healthy speech.…”
Section: Comparison Of Classifiers Performance On Depressed Speech Classificationsmentioning
confidence: 99%
“…We have reported that the timing related speech features can reflect the severity of depression. Speech rate, pause time, and response time showed significant associations with the total score of Hamilton Depression Rating Scale ( 15 , 16 ). We have also reported that body movement captured by infrared sensor can be reflective of depression severity ( 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Speech has great potential to be a source of such phenotypes and to provide unique preventative and predictive information about depression [5,6,7,8]. However, current research in this space is not without its limitations.…”
Section: Introductionmentioning
confidence: 99%